The Aesthetic of the Ego in the Poetry of Ibn al-Rumi - بن ساري, مسعود (Milev Journal of Research and Studies, 2023)
The poet's ego took a pivotal role in the poetic formation of Ibn al-Rumi, and the issue of the prominent presence of the ego was a phenomenon in his poetic collection, whose researchers and scholars did not meet its phenomena, to this day, to express the experience of the self with life, by repeating the word ego, and the multiplicity of its meanings and connotations, and the richness of the ways it was organized in his poetry. The ego becomes egos, loaded with meanings and psychological connotations, and aesthetic values, because of the diversity of intention and the different contexts, and the specificity of the ego has, such as the proud ego, the lover ego, the drunken ego, the weak weeping ego, The praising and the thankful ego. The satirical ego, and the traveling and the resident ego.